The Effectiveness of Educational Applications to Prevent Stunting Children (AECAS) on Perceptions of Stunting Prevention - Ika Nurfajriyani; Citra Setyo Dwi Andhini (Budapest International Research and Critics University, 2022)
As many as 21.9% or 149 million children under five in the world are stunted. Indonesia ranks fifth in the incidence of stunting in the world. The Educational Application to Prevent Stunting Children (AECAS) is a strategy developed to prevent stunting through an Android-based educational application. This study analyzes the effectiveness of the application of the education application to prevent stunting in children (AECAS) on the prevention of stunting. quantitative research with pre and post experimental approach with randomized controlled trial. The sample size in this study was 68 respondents. The average N-gain score for the intervention class (AECAS application method) was 56.98%, included in the moderately effective category, while the booklet method of 13.30% was in the ineffective category. There is a significant difference between the AECAS application method and the booklet method based on the different independent sample t test on the N Gain Score of perceptions of stunting prevention in the intervention and control groups with a p value of 0.0001. the educational application to prevent stunting (AECAS) is effective in preventing stunting by increasing the perception of stunting prevention.